"To be or not to be": the double consciousness of the Tamil Muslims during the early 20th century. Issue 2 (2nd April 2016) - Sherif, Yunush Ahamed Mohamed
ABSTRACT: When the nation building process was gaining momentum during the early 20th century, all the communities in British India had to participate in the process and the Muslims were no exception. Although the Muslim community in British India was as diverse as any other community, there was an attempt to unite its members under the identity of "Muslims" during the first half of the 20th century. But the Tamil Muslims remained aloof from the idea of an "Indian Muslim Community." They had a double consciousness of being a Tamil as well as a Muslim. They highlighted their "Tamilness" more than their "Muslimness." More than the Muslim League, their involvement with the Dravidian Movement was substantial. They supported both the movement for Dravidasthan as well as Pakistan. This paper will look into the process of "nation making, " particularly a "Muslim nation" and the anxiety of the Tamil Muslims during these processes. It will analyse the reasons behind the Tamil Muslims being alienated from the other Muslims, the British colonialist denying the identity of "pure" Muslims to the Tamil Muslims and their involvement in the Dravidian Movement.